Guwernantka carówny. Losy i perspektywa Jeanne Huc-Mazelet w świetle jej korespondencji z pobytu na rosyjskim dworze (1790-1804) - Strzelczyk , Agata (Studia Edukacyjne, 2023)
These article’s aim is to look into and analyze the letters written by Jeanne Huc-Mazelet, the governess of the Grand Duchess Maria Pavlovna of Russia (1790-1804). Born in Morges, Switzerland, Jeanne Huc-Mazelet was one of the few Swiss educators employed by the royal family of Russia to teach their children. She spent fourteen years in Russia and wrote many letters to her family in Switzerland. The letters are a valuable resource to study the everyday life of the Russian court and the princesses’ education. It also offers an interesting glimpse into the life of the author.